Analisis Perilaku Berisiko terhadap Kejadian Hipertensi Penduduk Usia Produktif Tahun 2023 - Tajmala, Bintana; Setiadi, Yaya (Politeknik Statistika STIS, 2025)
Hypertension is a non-communicable disease that affects a large portion of the Indonesian population, including individuals in the productive age group. The prevalence of hypertension among the productive age population continues to rise in line with unhealthy lifestyle changes. On the other hand, individuals in this age group are expected to engage in economic activities to support the needs of the non-productive population. This study aims to describe the general profile and characteristics of individuals with hypertension and to identify the factors influencing the incidence of hypertension among the productive age population in Indonesia in 2023. The analytical tools used are descriptive and inferential analyses using ordinal logistic regression, based on secondary data from the 2023 Indonesian Health Survey. The results show that 44.3 percent of the population is classified as prehypertensive, 17 percent as having stage 1 hypertension, 8.5 percent as having stage 2 hypertension, and the remaining 30.2 percent as having normal blood pressure. Significant risk factors include age group, gender, depression status, physical activity, salt intake, fiber and fat consumption, and smoking behavior. These findings highlight the need for promotive and preventive strategies for healthy lifestyle behavior in the productive-age population.